Study on Potential Ecological Corridor Identification and Anthropogenic Disturbance for Black and White Snub-nosed Monkey - He Chunlan; Cui Jing; Shen Jinxiang; Shi Xiaoqian; Huang Zhipang; Shen Yingzheng (E3S Web of Conferences, 2025)
The study on the connectivity among monkey groups is one of the critical issues in the conservation of the Black-and-white Snub-nosed Monkey (Rhinopithecus bieti, BWSM). Constructing ecological corridors is a vital strategy for restoring and maintaining the ecological connectivity of the BWSM’s habitat. This study utilized the Linkage Mapper tool, integrating the MaxEnt model, least-cost distance model, and gravity model, to extract and classify potential ecological corridors, identify potential ecological nodes, and analyze these corridors and nodes in terms of human disturbance index and land use/ cover. The results indicate that: 1) 53 ecological sources (3814.86 km²) were identified, with 42.79% located outside existing protected areas; 2) 97 potential ecological corridors, 136 ecological barrier points (666.38 km²), and 112 ecological pinch points (25.64 km²) were identified; 3) The number of corridor level, the primary, secondary and tertiary corridors were 22, 41, and 34. The corresponding areas of ecological barrier points and pinch points account for 0.39%, 15.06%, 84.55% and 2.70%, 18.82%, 78.48%, respectively; 4) Human activities and complex land cover types are the primary factors impeding the migration of the BWSM. Specifically, 46 potential corridors were disturbed by residential areas and roads, with a total disturbance index of 0.50. The disturbance index of third-level corridors (0.67) was significantly higher than the overall level. Furthermore, within a 50m corridor width and within barrier areas, the absolute proportions of unsuitable forest, grassland, and farmland increased landscape resistance to monkey migration. In the future, ecological corridor restoration can be carried out according to the priority of ecological circulation. From the corridor level, the primary corridor > secondary corridor > tertiary corridor. In terms of the location of the study area, the middle section > the southeast section> the north section. These findings provide a scientific basis for the planning, construction, and ecological restoration of BWSM corridors across their entire range.